2005
DOI: 10.1266/ggs.80.185
|View full text |Cite
|
Sign up to set email alerts
|

Differential and coordinated expression of Cbf and Cor/Lea genes during long-term cold acclimation in two wheat cultivars showing distinct levels of freezing tolerance

Abstract: The cold acclimation process in plants is primarily regulated through the signal transduction pathways that lead to the induction and enhancement of expression of different sets of Cor / Lea genes. Winter wheat 'Mironovskaya 808' (M808) exhibited a much higher level of freezing tolerance than spring wheat 'Chinese Spring' (CS), and the difference became clearer after the long-term cold acclimation. To understand the molecular basis of this cultivar difference, we isolated two CBF/DREB1 homologs, Wcbf2 , which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 49 publications
6
57
0
2
Order By: Relevance
“…Similar to previous studies reporting that CBF/ DREB gene expression is associated with the expression of P5CS and DNH-like genes under abiotic stress (Gilmour et al, 2000;Kobayashi et al, 2005;Kume et al, 2005), in both potato species, the constitutive overexpression of the ScCBF1 gene was also associated with P5CS and DNH10 transcript accumulation under in vitro drought stress (Figure 3). …”
Section: Differential Expression Of Sccbf1 Pyrroline-5-carboxylate Ssupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to previous studies reporting that CBF/ DREB gene expression is associated with the expression of P5CS and DNH-like genes under abiotic stress (Gilmour et al, 2000;Kobayashi et al, 2005;Kume et al, 2005), in both potato species, the constitutive overexpression of the ScCBF1 gene was also associated with P5CS and DNH10 transcript accumulation under in vitro drought stress (Figure 3). …”
Section: Differential Expression Of Sccbf1 Pyrroline-5-carboxylate Ssupporting
confidence: 89%
“…However, the precise function of these proteins remains unknown. In wheat, early Dehydrin expression has been associated with drought tolerant genotypes and CBF gene expression Kume et al, 2005). In Solanum species, such as tobacco and potato, DHN-like genes have been associated with cold tolerance and CBF gene expression (Pino et al, 2008).…”
Section: Differential Expression Of Sccbf1 Pyrroline-5-carboxylate Smentioning
confidence: 99%
“…6b). Kume et al (2005) found that the DBF1-type gene, TaWCBF2, displayed diVerential expression during long-term cold acclimation in two wheat cultivars in a manner similar to TaDREB1, a DBF2-type gene (Shen et al 2003). Genetic variation may result from diVerences in the regulatory motifs present in promoters in diVerent cultivars (TaAIDFa was isolated from winter wheat cv.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel expression of DHN and Cbf genes has been found in cold stress (e.g. Kume et al, 2005). Cbf and other cold responsive genes were found activated by ABA independent and ABA dependent pathways as well (Knight et al, 2004).…”
Section: Droughmentioning
confidence: 62%